Translation of Al-Fuzai’s Story ‘The Strike’ - Dohal, Gassim (Technium Social Sciences Journal, 2024)
Al-Fuzai portrays a dispute between a wife and her husband’s mother in ‘The Strike.’1 Every newlywed couple encounters this issue because a bridegroom typically likes to remain with his parents and is socially encouraged to do so in many Arab communities. As a result, the problem is cultural; translation may help in portraying new cultures. In ‘The Strike,’ Al-Fuzai discusses this social issue while criticizing the social setting a new bride is placed in. An environment that is conducive to everyone in the family exercising their rights and living comfortably and prosperously should be created; however, this is not the case in the story. One of Al-Fuzai’s literary works is ‘The Strike.’ It has been translated to introduce the writer to the readers of this journal. It also addresses a social issue that some individuals might not give enough thought to. Moreover, translation is a way to communicate and bridge the gaps among different cultures.